POLA DAKWAH TERHADAP PERUBAHAN SOSIAL (ANALISIS PEMBERIAN JENIS MAKANAN BERGIZI PADA ANAK) - SYAMSUDDIN AB (Jurnal Dakwah Tabligh, 2018)
Propagation Pattern Against Social Change (Analysis Provision of Food Nutrition In Children), this study aimed to describe briefly about the invitation and call the parents in nutrition feeding system in children and change the type of food the parents of children coast. Propaganda patterns in changes in the types of food in coastal communities, especially children in their development implications for improving the quality and health of children. This type of research is qualitative and entomology approach, with primary and secondary data sources, methods of data management through early studies, in-depth interviews, documentation. Qualitative data analysis is a process for preparing the data either classify patterns or themes, a category that can be interpreted researchers, while the analysis of the data by using a model of Miles and Huberman of data reduction (data reduction), presentation of data (data display), conclusion. The results of this research show about the social change process calls for the parents in nutrition feeding system on the growth of children, both the post-birth, type of food and diet, immunization, and in reinforced with religius the health of children.